Time as a key resource for the effective operation of the Russian agro-industrial complex in digital transformation context. Issue 3 (December 2021) - Gusev, V; Shlenov, Y; Chernegov, N; Tatochenko, I; Poletaeva, L
Abstract: The article discusses the features of the activities of enterprises of the Russian agro-industrial complex in digital transformation context. The main types of resources used by them for effective work are highlighted and the task is to study time as an intangible asset that can be used to increase the efficiency of activities. This category is considered from the standpoint of classical science, its definition is given and the main properties are highlighted. The necessity of studying time as a resource and its use in the work of enterprises as a factor in the growth of profitability has been substantiated. The analysis of classical and modern systems of organizing the work of enterprises, including their tools. Based on the analysis, it has been established that during the period of digital transformation of the economy and the agro-industrial complex, little attention is paid to time as a resource, and the rational use of resources needs to be improved. For this reason, the digitalization of the agro-industrial complex is considered as the main vector of the development of the complex. The main directions of its transition from the traditional form to new methods of work, its elements, ways of reducing errors and increasing the competitiveness of enterprises in this sector of the economy are shown. The main advantages of such a development are presented. In the course of further analysis, it was found that the time factor in the agro-industrial complex during the period of digital transformation plays a key role. Time has been proven to be both a factor and a resource. It is concluded that the competent use of all types of production resources in time allows to obtain a synergistic effect.